Immune Checkpoint Inhibitor-Associated Systemic Sclerosis in the Treatment of a Small Cell Lung Cancer Patient with Durvalumab: A Case Report - Li DH; Xiong XZ (Clinical, Cosmetic and Investigational Dermatology, 2024)
De-Hu Li, Xian-Zhi Xiong Department of Pulmonary and Critical Care Medicine, NHC Key Laboratory of Pulmonary Diseases, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of ChinaCorrespondence: Xian-Zhi Xiong, Email xxz0508@hust.edu.cnAbstract: As one of the key cancer treatment measures, immune-checkpoint inhibitors (ICIs) have revolutionized the treatment landscape of various cancers, including malignancies previously thought to be untreatable. Immune checkpoint inhibitors work by targeting the dysfunctional immune system, to enhance cancer-cell killing by CD8-positive T cells. Despite the beneficial effects of ICIs, these treatments are also linked to a novel class of side effects, termed immune-related adverse events (irAEs). Immune-related adverse events can affect multiple organ systems, such as endocrine, neurological, gastroenteric, dermatologic, ocular, hepatic, renal, and rheumatic ones. While variable in severity, irAEs can be associated with significant morbidity, mortality, cessation of ICI treatment and can be potentially life-threatening sometimes. Among varieties of irAEs, dermatological manifestations are frequently reported, since they can be easily observed. Here, we present a case of a 74-year-old patient with widespread fibrosis of skin, eventually diagnosed as diffuse cutaneous systemic sclerosis after the treatment with durvalumab for small cell lung cancer (SCLC). Prompt recognition and treatment of immune-checkpoint inhibitors-associated systemic sclerosis may help enhance tolerance to ICIs and ensure better performance in treating tumors.Keywords: systemic sclerosis, durvalumab, small cell lung cancer, immune checkpoint inhibitors, immune-related adverse events